PENGARUH PENDEKATAN KETERAMPILAN PROSES TERHADAP HASIL BELAJAR IPA PADA PESERTA DIDIK KELAS VIII SEMESTER GANJIL SMP NEGERI 10 YOGYAKARTA - Sampurno Aji (N A T U R A L: Jurnal Ilmiah Pendidikan IPA, 2016)
The aims of this research were to find out:  (1) the result of student’s achievement in science by using process skill approach. (2) To determine the differences in student’s achievement in science by using process skill approach and expository. The research used the quasi-experimental method. The data collection technique, the writer used documentation to know the students’ initial competency and used test technique to get data on the result of studying additives and addictives of science subject. The data analysis technique in this study used t-test. Descriptively, the result of this study showed that the inclination of learning natural science result at eight grade student in SMP Negeri 10 Yogyakarta in academic year 2013/2014 which through with skill process include in exellent/very high category, whereas the calss which learning by expository approach includes in good/high category. The calculation result of t-test from contril class and experiment gained tcount > ttable was 2,094 > 2,000 and the probality values (p) ≤ 0,05 at the 5% significance level was 0.040 ≤ 0.05, therefore comparatively there were significant diferences between the learning through process skill and expository approach, this means that there are the influences in teaching to the result through process skill to science subject achievment at eigth students on odd semester in SMP Negeri 10 Yogyakarta academic year 2014/2015.